Development of Handout Media to Facilitate the Problem-Solving Abilities of Algebraic Functions Derivative for Class XI Senior High School Students - Angelina Lopo; Aloisius Loka Son; Ferdinandus Mone; Javier Garcia-Gracia (Indonesian Educational Research Journal, 2024)
The aim of this study is to develop valid, practical, and handout media effectof. This type of study is research and development. This research uses Plom model which consists of five phases, namely preliminary investigation, design, realization/construction, test, evaluation and revision, and implementation. Subject in this study includes experts, teachers and 15 students of class XI Mathematics and Natural Sciences at one of the Senior High Schools in Kefamenanu city, Indonesia. The data collection techniques used were questionnaires and tests. The validator consists of one lecturer in mathematics education and one mathematics teacher who assessed the quality of the handout media and the results of the assessment were declared valid. The level of practicality after being tested on students obtained a presentation score 83.49% so it is categorized as very practical, and also based on effectiveness test results obtained 81% of student grades in the very effective category. Thus, you can It was concluded that the handout media developed could facilitate solving ability’s algebraic function derivative problems are very valid, very practical, and very effective.